PENGARUH HARGA, E-SERVICE QUALITY, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN NETFLIXDI JABODETABEK - Christina Elviyani (2022)
Netflix is a legal streaming service, a place to watch and enjoy movies and series from various countries with different genres. There are testimonials from customers who are dissatisfied with Netflix services, in terms of price, e-service quality, and promotions, so the purpose of this research is to find out, prove, and analyze the effect of price, e-service quality, and promotions on Netflix customer satisfaction in Jabodetabek. This research method is a quantitative research with the sampling technique used is purposive sampling. Data analysis techniques using descriptive statistical analysis and inferential statistical analysis. The source of this research is primary data by distributing questionnaires in the form of Google Forms online. The test equipment used for this research is SmartPLS 4.0 software. The respondents collected were 121 Netflix subscribers in Jabodetabek. The results of the study show that the three factors, price, e-service quality, and promotion, have a positive and significant impact on customer satisfaction. The path coefficient value proves that price has an effect of 0.271, e-service quality of 0.301, and promotion has an effect of 0.298. The dominant factor that influences it is e-service quality of 0.301. The Adjusted R Square test result of 53.5% shows that the contribution of the price, e-service quality, and promotion variables together can represent the customer satisfaction variable, while 46.5% is explained by other factors.